2015
DOI: 10.1142/s1363919615500371
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Diffusion of Wind Power Across Countries

Abstract: In this paper, we analyse the diffusion mechanism of wind power over the last two decades in the leading countries, namely China, the United States, Germany, India and Spain. For each country, three prominent models of technology diffusion (Logistic, Bass and Gompertz) were fitted and the best model is identified based on AIC, BIC and adjusted R 2 criteria. The selected diffusion model in each case is then characterised with respect to the policy mechanisms. Often, research follows the "one size fits all" appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Infrastructure has more weight than raw material characteristics due to inability to use raw material owing to infrastructure issues. Countries including India and China are facing issues related to load management in terms of managing reserve capacity and underutilization of networks which has resulted in utilities refusing to accept wind power by the grid 3 . Germany was able to increase its wind energy share in total energy by addressing some factors pertaining to infrastructural issues related to locallevel distribution systems 25 .…”
Section: Local Peripheral Factor Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrastructure has more weight than raw material characteristics due to inability to use raw material owing to infrastructure issues. Countries including India and China are facing issues related to load management in terms of managing reserve capacity and underutilization of networks which has resulted in utilities refusing to accept wind power by the grid 3 . Germany was able to increase its wind energy share in total energy by addressing some factors pertaining to infrastructural issues related to locallevel distribution systems 25 .…”
Section: Local Peripheral Factor Weightsmentioning
confidence: 99%
“…Studies have shown that the decision to install wind power plants is influenced by national 3 , state 4 and local factors 5 . Here we focus on local factors as they are more closely associated with on-field characteristics.…”
mentioning
confidence: 99%